The Effect of Progressive Muscle Relaxation (PMR) on Pain in Breast Cancer Patients in the Outpatient Clinic - Sharla Rahma Danty, Annisa; Maryuni, Sri; Antoro, Budi (Java Nursing Journal, 2026)
Background: Breast cancer is a common disease that often causes chronic pain, which negatively impacts patients' quality of life. Progressive Muscle Relaxation (PMR) is a non-pharmacological intervention that has the potential to reduce pain levels through progressive muscle relaxation. Purpose: This study aims to determine the effect of PMR administration on the pain quality of breast cancer patients in the outpatient clinic of Dr. H. Abdul Moeloek Regional General Hospital, Bandar Lampung Methods: The method used was quantitative with a pre-experimental design, specifically a pre-test-post-test design. The population consisted of 490 patients, with a sample of 18 respondents selected using purposive sampling. The research was conducted from February 9 to March 10, 2025, at the Dr. H. Abdul Moeloek Bandar Lampung Regional General Hospital Polyclinic Results: The results showed a decrease in the average pain scale from 5.17 before the intervention to 2.39 after PMR administration. The Wilcoxon test produced a p-value of 0.000, indicating a significant effect of PMR on pain reduction in breast cancer patients Conclusion: This study supports the use of Progressive Muscle Relaxation as an effective non-pharmacological therapy to reduce pain in breast cancer patients, thereby improving their quality of life and comfort during treatment Relevance to clinical practice: Nurse-led progressive muscle relaxation can be integrated into outpatient breast cancer care as a brief, low-cost adjunct that may lower pain intensity, enhance comfort, and support individualized nonpharmacologic symptom management.